2014
DOI: 10.4209/aaqr.2013.09.0290
|View full text |Cite
|
Sign up to set email alerts
|

Car Engines Air Filters. A Useful Ambient Air Sampler and/or a Possible Hazardous Waste?

Abstract: Car-engine air filters (CAFs) have been recently used as inexpensive alternative air sampling media for hydrophobic organic compounds such as polycyclic aromatic hydrocarbons, polychlorinated dibenzo-p-dioxins and furans and also for heavy metals. This "active-passive" sampling methodology is a promising way for urban air monitoring, being able to offer invaluable advantages. Two approaches have been proposed for the estimation of the air volume that passes through the CAFs and are herein reviewed and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Several studies (Khalili et al, 1995;Marr et al, 1999) have identified these vehicles as major sources of PAH emissions in the environment. These aromatic compounds' formation mechanisms in the mobile sources are either through pyrosynthesis or survival mechanism and the emissions depends on several factors including the engine type, fuel composition, load and age, mileage, PAH content in lubricant oil, lubricant oil combustion, driving mode and emission control devices such as air filters (Ravindra et al, 2008;Katsoyiannis, 2014). These factors are addressed in more detail in the subsequent sections.…”
Section: Pah Emissions From Mobile Sourcesmentioning
confidence: 99%
“…Several studies (Khalili et al, 1995;Marr et al, 1999) have identified these vehicles as major sources of PAH emissions in the environment. These aromatic compounds' formation mechanisms in the mobile sources are either through pyrosynthesis or survival mechanism and the emissions depends on several factors including the engine type, fuel composition, load and age, mileage, PAH content in lubricant oil, lubricant oil combustion, driving mode and emission control devices such as air filters (Ravindra et al, 2008;Katsoyiannis, 2014). These factors are addressed in more detail in the subsequent sections.…”
Section: Pah Emissions From Mobile Sourcesmentioning
confidence: 99%
“…Zhang et al [12] and Katsoyiannis et al [13] suggested that car air filters (CAFs) from taxis could act as “moving” high volume air samplers to provide city-integrated air concentrations with low variability for particle-bound contaminants. CAFs, which are necessary components of automobiles, are usually composed of polyurethane and other fiber-like materials, most frequently cotton, foam, or paper.…”
Section: Introductionmentioning
confidence: 99%
“…Since many years ago, vehicular emissions have been identified as one of the main PAH sources to the environment (Khalili et al 1995;Marr et al 1999). Formation mechanisms of PAHs in mobile sources are through pyrosynthesis and emissions depend on some factors such as type of engine, composition of fuel, mileage, PAH content in lubricant oils, lubricant oil combustion, ways of driving, and control devices of emissions like air filters (Katsoyiannis 2014;Ravindra et al 2008).…”
Section: Pah Diagnostic Ratiosmentioning
confidence: 99%